"It gives me a wake up call"—It is time to implement athlete health monitoring within the Para sport context - Fagher, K.; Badenhorst, M.; Kunorozva, L.; Derman, W.; Lexell, J (Scandinavian Journal of Medicine & Science in Sports, 2022)
Objectives The aim of this study was to explore elite Para athletes' and coaches' perceptions of experiences of athlete health monitoring.